PELATIHAN EKOWIRAUSAHA PRODUK DETERGEN DAN EDUKASI HUKUM DAGANG DI DESA AIR NANINGAN - Agung Abadi Kiswandono; Sumiharni Sumiharni; Yulia Kusuma WARDANI; Heni Siswanto; Munaris Munaris (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
Air Naningan is a village in the district of Air Naningan that has strategic access to the business center (the Air Naningan market). The location of business and marketing for local products can also be found along the road after Pringsewu to Wonosobo, Semaka towards Pesisir Barat and Lampung Barat. It provides benefits to the community to increase entrepreneurship into an eco-entrepreneurship-based. One of the products which is needed by many people and easily made with cheap capital is detergent. Although this product is easy to get, most people consider to buy the product at a cheaper price. The main objective of this community service activities is to assist PKK group of Air Naningan village for producing detergents. In addition, this activities also make the assistance to partner groups in the form of training and practice, brand counseling and labeling and trade law education. It is found that the result of the dedication can increase the participant's knowledge by 65.5% (21.08% to 86.58%). Moreover, the partner group has the ability to make detergent products.